THE INFLUENCE OF THE PROBLEM BASED LEARNING MODEL ON THE CRITICAL THINKING ABILITY OF CLASS V STUDENTS - Putri, Aprilia Eka; Rahmi, Laili (PD PGMI se Indonesia, 2024)
In learning, educators play a very important role in helping students solve problems, therefore teachers must encourage students to actively participate in learning by using the Ptoblem Based Learning learning model. This study aims to answer the hypothesis of a significant influence on students' critical thinking skills by using learning models other than lecture methods, such as the problem based learning (PBL) learning model in grade V of the Social Sciences subject and the material 'Technology in Life' SDN 190 Pekanbaru. This study applies a quantitative model with a research design used is one group only pretest-posttest. In this study, the population was all grade V at SDN 190 Pekanbaru in the 2024/2025 academic year. The sample selection used total sampling by collecting a sample of 50 students from grade V. The method used in this study is the data collection method, with the action test and documentation method. The data analysis technique in this study used a hypothesis test with the Independent Sample T-test. Based on the findings, the Sig. value was obtained. (2-tailed) of <0.001 <0.05, it can be concluded that there is an influence of the problem based learning model on critical thinking skills in technology material in class V life. It can also be seen that there is an average or mean value in the control class posttest of 66.23 and in the experimental class of 86.21.